Tindak Pidana Kepemilikan Bahan Peledak dalam Prespektif Hukum Pidana Islam - Jamila Jamila (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2020)
Abstract: This paper aims to determine the crime of explosives possession from the perspective of Islamic Criminal law. The results of this study concluded that the Sidoarjo District Court judge used the legal basis of UUDrt No. 12/1951 article 1 dan 3 Jo article 55 (1) jo article 64 (1) penal code in apprehending the perpetrators of explosive ownership cases. Before deciding the case, the Sidoarjo District Court judge had considered aggravating and mitigating factors. Based on the above, the decision given by the Sidoarjo District Court judge had fulfilled the justice and deterrent aspect to the perpetrators of the crime of explosives possession. It is in line with Islamic criminal law because the sanctions imposed contained the essence of benefit for community life and were beneficial to legal authority or shari'ah itself.